Principles and practice of toxicology in public health - Richards, Ira S. (Ira Steven) 1948-; Bourgeois, Marie M. (Jones & Bartlett Learning, 2014)
All public health professionals should have some level of knowledge of the basic principles of Toxicology. Whether dealing with issues as diverse as a workers' compensation claim for a job-related exposure and injury or the removal of toxic wastes from an urban community, public health professionals must be able to communicate with each other, the public, and our political leaders concerning how chemicals can, and the conditions under which they may, realistically produce harm. Principles and Practice of Toxicology in Public Health provides students with an understanding of the nature and scope of the discipline, so that they may be prepared to participate in a meaningful way in the often highly visible problem-solving and decision-making processes required of public health professionals. In four sections, it offers an introduction to the field, as well as the basics of toxicology principles, systemic toxicity, and toxicology practice. The text is immediately readable for the student with little technical background. The Second Edition is a thorough update that has been expanded with a new chapter on endocrine toxicology.